Correlation between standardized uptake value of 68Ga-DOTA-NOC positron emission tomography/computed tomography and pathological classification of neuroendocrine tumors - Kaewput, Chalermrat; Suppiah, Subapriya; Vinjamuri, Sobha (Wolters Kluwer - Medknow Publications and Media, 2018)
The aim of our study was to correlate tumor uptake of 68Ga-DOTA-NOC positron emission tomography/computed tomography (PET/CT) with the pathological grade of neuroendocrine tumors (NETs). 68Ga-DOTA-NOC PET/CT examinations in 41 patients with histopathologically proven NETs were included in the study. Maximum standardized uptake value (SUVmax) and averaged SUV SUVmean of “main tumor lesions” were calculated for quantitative analyses after background subtraction. Uptake on main tumor lesions was compared and correlated with the tumor histological grade based on Ki-67 index and pathological differentiation. Classification was performed into three grades according to Ki-67 levels; low grade: Ki-67 <2, intermediate grade: Ki-67 3–20, and high grade: Ki-67 >20. Pathological differentiation was graded into well- and poorly differentiated groups. The values were compared and evaluated for correlation and agreement between the two parameters was performed. Our study revealed negatively fair agreement between SUVmax of tumor and Ki-67 index (r = −0.241) and negatively poor agreement between SUVmean of tumor and Ki-67 index (r = −0.094). SUVmax of low-grade, intermediate-grade, and high-grade Ki-67 index is 26.18 ± 14.56, 30.71 ± 24.44, and 6.60 ± 4.59, respectively. Meanwhile, SUVmean of low-grade, intermediate-grade, and high-grade Ki-67 is 8.92 ± 7.15, 9.09 ± 5.18, and 3.00 ± 1.38, respectively. As expected, there was statistically significant decreased SUVmax and SUVmean in high-grade tumors (poorly differentiated NETs) as compared with low- and intermediate-grade tumors (well-differentiated NETs). SUV of 68Ga-DOTA-NOC PET/CT is not correlated with histological grade of NETs. However, there was statistically significant decreased tumor uptake of 68Ga-DOTA-NOC in poorly differentiated NETs as compared with the well-differentiated group. As a result of this pilot study, we confirm that the lower tumor uptake of 68Ga-DOTA-NOC may be associated with aggressive behavior and may, therefore, result in poor prognosis.